Beyond the Borders: The Significance of Frontiers between Central Balkans’ Roman Provinces in the Context of Roman Art - Gavrilović Vitas, Nadežda (Actual Problems of Theory and History of Art, 2019)
Roman conquest in the 1st century, upon which tribal communities were organized into administrative units. The fact that the boundaries of pre-Romantribal territories didn’t correspond in total with the areas of the newly formed Roman provinces, led to frequent influences from neighbouring provinces and the blending of Roman art with local traits in the artistic sphere. Although in the 1st century different types of sculpture (cult, monumental and honorary) were present, throughout the whole period of the Roman reign cult sculptures and statues were the most numerous. Tracing the development of the art in the territory of Central Balkans’ Roman provinces, it is clear that the northern parts were more under the Roman influence as the consequence of indigenous population more readily adapting to the process of Romanisation, while the southern parts of the Central Balkans area were more influenced by the Greek culture with which they were in contact from as early as the middle of the 7th century B.C. Sculptures, statues and reliefs were modelled upon Roman art canons, copying classical Greek and Hellenistic art, in bigger centres like Ratiaria, Singidunum, Viminacium, Naissus, Scupi etc. and localities along the Danube limes. At the same time, in the interior of the Central Balkans’ provinces, works of art were manufactured upon Roman canons but with local traits. These were mainly recognized in the simplicity, frontality and linearity of the art works. This is particularly visible in the western and south-western parts of the aforementioned territory, as in some of the localities in eastern parts of the area. During the 2nd and the 3rd centuries, beside skilful artisans from Greece, Asia Minor and the Mediterranean, who came and worked in bigger centres, local workshops also produced different kinds of artworks, copying Roman types in a more or less successful way. During the 3rd century particularly, different cultural and artistic influences met and blended, often transcending the administrative borders of the provinces, thus the forthcoming iconographic syncretism was present in the 4th century as well. From the end of the 3rd and during the 4th century, rich aristocrats,local elite and emperors ordered high quality works for decorating their estates and villas, following aesthetic criteria established in other eastern and western provinces. In the art works from that period, beside certain schematism and linearity in the modelling, a blending of similar iconographic details is emphasizedas the presence of local artistic traits. Therefore, the continuance of manufacturing of the sculpture by copying classical Greek works of art and of the locally produced works of art with traits of indigenous material cultures is present until the end of the Roman reign.